Genetic analysis on growth of body dimensions in Muzaffarnagari sheep - Mandal, Ajoy; Rout, P K; Roy, R; Sinha, N K (The Indian Journal of Animal Sciences, 2007)
Data on body length, height at withers and heart girth at birth, 3, 6, 9 and 12 months of age were collected from 4287 Muzaffnagari sheep, an important mutton breed of India, born between 1978 to 2001, maintained at the Central Institute for Research on Goats, Makhdoom, Mathura, to study the effect of important environmental factors on these traits. Significant differences among sires existed within the breed for all the traits. The lambs maintained under individual feeding (ad lib, feeding) grew faster and were larger in all body dimensions and heavier weight than lambs reared under group feeding on each occasion. There were significantly marked periodic differences in all body dimensions and weights of lambs at all the ages. The parity of dam had significant effect on body size at birth and 3 months of age. The season of birth of lamb significantly affected the growth of some of the body dimensional traits under study. The sex and birth status of lambs were also significant for all body measurements. Males were heavier than females for all traits at all stages of growth. Single born lambs had a distinct advantage over those born in multiple births at all the stages of growth up to 1 year of age. The regression of weight of dam at lambing showed significant effect on all the traits at all the ages.bThe heritabilities of all body dimensions were moderate to high in magnitude except at birth. Genetic correlations among the linear measurements were medium (0.25±0.17) to high (0.96±0.02) from birth to 1 year of age. The genetic and phenotypic correlations among body dimensions and body weights were positive and moderate to high in magnitude. The highest genetic correlations at weaning, 6 and 9 months of age between heart girth and body weight were noticed.